Endometrial Cancer Patients: A Cohort Previous to Changes in Tumour Behaviour and Treatment Strategies. (18th December 2011) - Tournois, F. K. L.; Mertens, H. J. M. M.
Abstract : Nowadays, the incidence of endometrial cancer is rising, especially of high-grade endometrial tumours. Recently, the FIGO classification of endometrial cancer has changed worldwide. Besides that, treatment strategies are changing. The purpose of this study was to analyse the adherence to the national guidelines of cancer treatment and to analyse patterns of disease relapse and survival. We focused on a group of patients (n = 191 ) with endometrial cancer, in a time period in which new treatment strategies are not yet completely implemented. Because of multiple upcoming changes in patient characteristics, tumour classification, as well as treatment regimens, a more heterogeneous cohort of patients diagnosed with endometrial cancer will appear. From now on, all those changes will have their effects on the followup of conventional endometrial cancer treatment. In our opinion, it is, therefore, valuable to have the current, more homogenous, cohort clearly described.